"Two-in-one" organic–inorganic hybrid MnII complexes exhibiting dual-emissive phosphorescence. Issue 21 (17th May 2018) - Berezin, Alexey S.; Samsonenko, Denis G.; Brel, Valery K.; Artem'ev, Alexander V.
Abstract : A family of "two-in-one" dual-emissive complexes, [Mn(L)3 ]MnHal4, containing octahedral and tetrahedral Mn 2+ ions in the single structure, is introduced. Abstract : Unprecedented organic–inorganic hybrid complexes, [Mn(L)3 ]MnHal4, containing both four- and hexacoordinated Mn 2+ ions were synthesized by reacting MnCl2 or MnBr2 with bis(phosphine oxide) ligands (L) such as dppmO2, dppeO2, and 2, 3-bis(diphenylphosphinyl)-1, 3-butadiene (dppbO2 ). In the [Mn(L)3 ] 2+ cation of the complexes, the Mn 2+ ion features a [MnO6 ] octahedral coordination environment ( O h ), and the [MnHal4 ] 2− anion adopts a tetrahedral geometry ( T d ). These "two-in-one" complexes exhibit strong long-lived luminescence ( τ av = 12–15 ms at 300 K) having interesting thermochromic behavior attributed to the thermal equilibrium between two emission bands. So, in an emission spectrum of the typical complex [Mn(dppbO2 )3 ]MnBr4, the intense "red" ( ca. 620 nm) and weak "green" ( ca. 520 nm) bands, originating from Mn 2+ ions in O h and T d environments, respectively, are observed. Cooling from 300 to 77 K simultaneously leads to (i) redshift of both bands by ca. 20 nm, (ii) increasing their intensities, and (iii) causing a substantial change of their integral intensity ratio from about 4 : 1 to 2 : 1. As a result, the colour of the emission changes from orange (CIE 0.56, 0.45) at 300 K to deep red (CIE 0.62, 0.39) at 77 K. This behavior was rationalized using steady-state and time-resolved fluorescent spectroscopy at various temperatures. The high photoluminescence quantum yields (up to 61% at 300 K) and fascinating dual-emissive phosphorescence coupled with high thermal stability and solubility suggest a high potential of this novel class of emissive Mn 2+ complexes as promising emitters for OLED devices and potential stimuli-responsive materials.